(untitled) (Communications in Computational Physics, 2014)
Numerical simulation of stratified flow of two fluids between two infinite parallel plates using the Moving Particle Semi-implicit (MPS) method is presented. The developing process from entrance to fully development flow is captured. In the simulation, the computational domain is represented by various types of particles. Governing equations are described based on particles and their interactions. Grids are not necessary in any calculation steps of the simulation. The particle number density is implicitly required to be constant to satisfy incompressibility. The weight function is used to describe the interaction between different particles. The particle is considered to constitute the free interface if the particle number density is below a set point. Results for various combinations of density, viscosity, mass flow rates, and distance between the two parallel plates are presented. The proposed procedure is validated using the derived exact solution and the earlier numerical results from the Level-Set method. Furthermore, the evolution of the interface in the developing region is captured and compares well with the derived exact solutions in the developed region.